A Moment Of Fortitude: The Chase County Courthouse - Christy Davis (Symphony in the Flint Hills, 2016)
Can a building determine the fate of an entire community? The Chase County Courthouse did. Cottonwood Falls had been the seat of Chase County since 1859, but by 1871, with the Santa Fe Railroad making tracks between Emporia and Newton, the small city couldn’t chance its future on the battered log cabin that had served as the courthouse since the early days of the Civil War.
Keywords: courthouse; New England Emigrant; Second Empire Style; natural resources; native stone; monument; pioneer; fortitude; VIEW FROM CHASE COUNTY COURTHOUSE; Mark A. Fisher; FLINT HILLS ORIGAMI CRANES & NEST; Chiyoko Myose